2017
DOI: 10.1364/josab.34.000764
|View full text |Cite
|
Sign up to set email alerts
|

Limits of coherent supercontinuum generation in normal dispersion fibers

Abstract: We study the largely unexplored transition between coherent and noise-seeded incoherent continuum generation in all-normal dispersion (ANDi) fibers and show that highly coherent supercontinua with spectral bandwidths of one octave can be generated with long pump pulses of up to 1.5 ps duration, corresponding to soliton orders of up to N = 600. In terms of N, this corresponds to an approximately 50 times increase of the coherent regime compared to anomalous dispersion pumping. In the transition region between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
139
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(148 citation statements)
references
References 50 publications
8
139
1
Order By: Relevance
“…2(a)). In particular, good coherence is seen to require pulse durations below 100 fs, which is an order of magnitude shorter than the corresponding limit found without this even weak laser amplitude noise of 0.3% [12,14].…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…2(a)). In particular, good coherence is seen to require pulse durations below 100 fs, which is an order of magnitude shorter than the corresponding limit found without this even weak laser amplitude noise of 0.3% [12,14].…”
Section: Resultsmentioning
confidence: 70%
“…In ANDi SC generation, it has been shown that the pulse duration, fiber length, and peak power have a critical influence on the noise properties [12,14], e.g., the anticipated coherent spectra are only obtained for sufficiently short pulse durations and fiber lengths. To see the effect of pump laser amplitude noise on the coherence and the requirements on the fiber length and pulse parameters, we simulate a wide parameter space and calculate for each case the spectrally averaged coherence given by [12,20]:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations